A Novel Bunyavirus Discovered in Oriental Shrimp (Penaeus chinensis) - Xuan Dong (Frontiers Media S.A., 2021)
Herein, we describe a novel bunyavirus, oriental wenrivirus 1 (OWV1), discovered in moribund oriental shrimp (Penaeus chinensis) collected from a farm in China in 2016. Like most bunyaviruses, OWV1 particles were enveloped, spherical- to ovoid-shaped, and 80–115 nm in diameter. However, its genome was found to comprise four segments of (-)ssRNA. These included an L RNA segment (6,317 nt) encoding an RNA-directed RNA polymerase (RdRp) of 2,052 aa, an M RNA segment (2,978 nt) encoding a glycoprotein precursor (GPC) of 922 aa, an S1 RNA segment (1,164 nt) encoding a nucleocapsid (N) protein of 243 aa, and an S2 RNA segment (1,382 nt) encoding a putative non-structural (NSs2) protein of 401 aa. All the four OWV1 RNA segments have complementary terminal decanucleotides (5′-ACACAAAGAC and 3′-UGUGUUUCUG) identical to the genomic RNA segments of uukuviruses and similar to those of phleboviruses and tenuiviruses in the Phenuiviridae. Phylogenetic analyses revealed that the RdRp, GPC, and N proteins of OWV1 were closely related to Wēnzhōu shrimp virus 1 (WzSV-1) and Mourilyan virus (MoV) that infect black tiger shrimp (P. monodon). Phylogenetic analyses also suggested that OWV1 could be classified into a second, yet to be established, species of the Wenrivirus genus in the Phenuiviridae. These wenriviruses also clustered with Wenling crustacean virus 7 from shrimps and bunya-like brown spot virus from white-clawed crayfish. Of note there were no homologs of the NSs2 of OWV1 and MoV/WzSV-1 in GenBank, and whether other crustacean phenuiviruses also possess a similar S2 RNA segment warrants further investigation. In addition, we established a TaqMan probe-based reverse-transcription quantitative PCR method for detection of OWV1, and it was detected as 1.17 × 102—1.90 × 107 copies/ng-RNA in gills of 23 out of 32 P. chinensis samples without an obvious gross sign. However, the discovery of OWV1 highlights the expanding genomic diversity of bunyaviruses.